2021
DOI: 10.2147/copd.s297089
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of COPD Patients According to COPD Assessment Test (CAT) Score Level: Cross-Sectional Study

Abstract: Purpose The chronic obstructive pulmonary disease (COPD) assessment test (CAT) is widely used to assess the impact of COPD symptoms on health status. Whilst the CAT consists of eight different items, details on the distribution of each item are limited. This study aimed to investigate the distribution and clinical implication of each CAT item, stratified by CAT severity group, in stable COPD patients. Patients and Methods This was a cross-sectional study at a single ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Although the CAT was developed to be unidimensional and without subdomains, 8 the items can be pragmatically grouped into two groups based on their content: cough, phlegm, chest tightness, and breathlessness as ‘pulmonary items’; and activities, confidence, sleep, and energy as ‘extra-pulmonary items’. 18 , 20 In our study, scores for phlegm, chest tightness, and breathlessness items of the CAT remarkably improved after short-term bronchodilator therapy in all patients. Scores for items five through eight (activities, confidence, sleep, and energy), classified as ‘extra-pulmonary’, did not show any change.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Although the CAT was developed to be unidimensional and without subdomains, 8 the items can be pragmatically grouped into two groups based on their content: cough, phlegm, chest tightness, and breathlessness as ‘pulmonary items’; and activities, confidence, sleep, and energy as ‘extra-pulmonary items’. 18 , 20 In our study, scores for phlegm, chest tightness, and breathlessness items of the CAT remarkably improved after short-term bronchodilator therapy in all patients. Scores for items five through eight (activities, confidence, sleep, and energy), classified as ‘extra-pulmonary’, did not show any change.…”
Section: Discussionsupporting
confidence: 56%
“… 15 17 Recent studies have shown that each CAT item contains additional information and contributes differently to the total score. 18 20 However, to the best of our knowledge, there are a few data primarily focusing on changes in each CAT item after bronchodilator therapy initiation and its association with other clinical factors. Thus, we investigated changes in individual CAT scores after short-term bronchodilator therapy among treatment-naïve patients with COPD and compared lung function, mMRC dyspnea, and exacerbations between patients whose CAT scores improved and those whose CAT scores did not.…”
Section: Introductionmentioning
confidence: 99%
“…In our prognosis models, dyspnoea and age were also significantly associated with survival. It has long been known that the degree of dyspnoea has significantly more prognostic relevance than grading according to lung function values in patients with COPD [33][34][35][36]. Dyspnoea is a substantial correlate of hyperinflation in patients with COPD, which often results in dynamic hyperinflation and disturbance of ventilatory efficiency [2].…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of our study are consistent with previous publications demonstrating that patients with elevated CAT scores frequently experienced acute exacerbations, these studies primarily considered total CAT scores [18,29,30], and a scarcity of studies have focused on each component of the CAT. Recent studies showed that patients with higher total CAT scores had a greater proportion of highly scored items related to non-respiratory issues [31,32]. Gil and colleagues [32] reported that CAT items related to activity and confidence showed particularly rapid deterioration in patients with high CAT impact.…”
Section: Discussionmentioning
confidence: 99%